2018
DOI: 10.1186/s12974-018-1060-5
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of VCE-003.2, a cannabigerol quinone derivative, against inflammation-driven neuronal deterioration in experimental Parkinson’s disease: possible involvement of different binding sites at the PPARγ receptor

Abstract: BackgroundNeuroprotection with cannabinoids in Parkinson’s disease (PD) has been afforded predominantly with antioxidant or anti-inflammatory cannabinoids. In the present study, we investigated the anti-inflammatory and neuroprotective properties of VCE-003.2, a quinone derivative of the non-psychotrophic phytocannabinoid cannabigerol (CBG), which may derive its activity at the peroxisome proliferator-activated receptor-γ (PPARγ). The compound is also an antioxidant.MethodsWe evaluated VCE-003.2 in an in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
71
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 54 publications
8
71
0
1
Order By: Relevance
“…However, another CBD derivative, VCE-003, induces PPARγ-mediated antioxidant and anti-inflammatory activity that prevents neuronal damage caused by inflammation in the Parkinson's mouse model (intravascular LPS injection). The same effect was seen in the in vitro cellular model of neurological inflammation (BV2 cells exposed to LPS and M-213 cells treated with media prepared from BV2 cells exposed to LPS) [131].…”
Section: Ppar γ Receptorsupporting
confidence: 61%
“…However, another CBD derivative, VCE-003, induces PPARγ-mediated antioxidant and anti-inflammatory activity that prevents neuronal damage caused by inflammation in the Parkinson's mouse model (intravascular LPS injection). The same effect was seen in the in vitro cellular model of neurological inflammation (BV2 cells exposed to LPS and M-213 cells treated with media prepared from BV2 cells exposed to LPS) [131].…”
Section: Ppar γ Receptorsupporting
confidence: 61%
“…VCE‐003.2 also attenuated TNF‐α and L‐1β secretion but from BV2 mouse microglial cells (5 μM) and astroglial cells (1 and 5 μM; Díaz‐Alonso et al, 2016; García et al, 2018; Rodríguez‐Cueto et al, 2018). Díaz‐Alonso et al (2016) and García et al (2018) deduced that VCE‐003.2 did not mediate its protective effects via CB 1 or CB 2 receptors due to poor binding affinity ( K i > 40 μM) and both groups found that VCE‐003.2 was an agonist at PPARγ (IC 50 of 1.2 μM).…”
Section: Resultsmentioning
confidence: 97%
“…Nine studies included in vitro data, and eight included in vivo data on CBG and its derivatives that are formed by the oxidation of CBG (Carrillo‐Salinas et al, 2014; Díaz‐Alonso et al, 2016; García et al, 2018). VCE‐003 and VCE‐003.2 have displayed increased affinity for PPARγ, thus maintaining their anti‐inflammatory properties while having little affinity for CB 1 and CB 2 receptors (VCE‐003 K i > 40 μM for CB 1 and K i > 1.76 μM CB 2 , Granja et al, 2012, and VCE‐003.2 K i > 40 μM for both CB 1 and CB 2 , García et al, 2018). All studies except one reported a positive effect of CBG, VCE‐003, or VCE‐002.3, compared with control in the disease model being studied.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations